2023
DOI: 10.1038/s41576-022-00568-4
|View full text |Cite
|
Sign up to set email alerts
|

Human-specific genetics: new tools to explore the molecular and cellular basis of human evolution

Abstract: Our ancestors acquired morphological, cognitive and metabolic modifications that enabled humans to colonize diverse habitats, develop extraordinary technologies and reshape the biosphere. Understanding the genetic, developmental and molecular bases for these changes will provide insights into how we became human. Connecting human-specific genetic changes to species differences has been challenging owing to an abundance of low-effect size genetic changes, limited descriptions of phenotypic differences across de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 343 publications
(428 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, these candidates can serve as a basis for reconstructing the phenotypic characteristics of Denisovans and shedding light on the adaptive mechanisms within this archaic human group. These identified candidates present a valuable resource for functional testing through experimental assays 59,60 and can collaborate with prediction algorithms to further explore their phenotypic significance 61 . Ultimately, a significant expansion of available association data 62 will be a crucial component in advancing our understanding of the phenotypic potential of Denisovan DNA and its contribution to the adaptation of modern humans.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these candidates can serve as a basis for reconstructing the phenotypic characteristics of Denisovans and shedding light on the adaptive mechanisms within this archaic human group. These identified candidates present a valuable resource for functional testing through experimental assays 59,60 and can collaborate with prediction algorithms to further explore their phenotypic significance 61 . Ultimately, a significant expansion of available association data 62 will be a crucial component in advancing our understanding of the phenotypic potential of Denisovan DNA and its contribution to the adaptation of modern humans.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic changes that drive evolution include gene birth (Kaessmann, 2010), gene loss (Albalat and Canestro, 2016), and changes in regulatory sequences (Prud’homme et al, 2007). The limited genomic differences but substantial phenotypic and behavioral divergence between humans and other hominids make what genomic changes at what time have critically driven human evolution an enduring puzzle (Anton et al, 2014; Pollen et al, 2023). Although waves of studies have identified genes promoting human brain development (Evans et al, 2005; Fiddes et al, 2018; Mekel-Bobrov et al, 2005; Pinson et al, 2022; Suzuki et al, 2018), conclusions from gene birth-centered studies are controversial (Currat et al, 2006; Timpson et al, 2007; Yu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Using human-specific genomic changes to inform studying human-specific features has been a hot topic ( Pollen et al, 2023 ) since the first discovery of human accelerated regions (HARs) that were highly conserved across vertebrates but with an accelerated rate of evolution from chimpanzees to humans in nucleotide substitution ( Pollard et al, 2006 ). The roles of HARs have been confirmed in regulation of human-specific morphological features such as limb and brain development ( Prabhakar et al, 2008 ; Boyd et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%